Min al-Makātib ilā al-Faḍā’āt al-Saybirāniyyah: Fa‘āliyyat Barnāmaj al-Irsyād Mā Qabla al-Zawāj ‘Abra Minaṣṣāt al-Tawāṣul al-Ijtimā‘iyyah - Jamal, Fauzun; Sujoko, Imam; Hamna, Waleed Obaid Adam (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2024)
The progress of communication technologies, especially post-Covid-19, has changed general behavior patterns and premarital rehabilitation programs. Traditionally held at religious affairs offices (KUA), these programs are now frequently found on social media platforms like Instagram, YouTube, and Facebook with various type. This research was presented to answer a valid question about premarital guidance program chapters via social media, how they were applied and whether they demonstrated good effectiveness. By employing qualitative study, the research found that the premarital guidance program through the social network provide sufficient and innovative materials for their followers and conducting in an appropriate manner and advanced way. As for the effectiveness of the pre-marriage guidance program classes through social media platforms, the result showed that they have good effectiveness, either in terms of the participants’ assimilation of the materials, or in terms of organizing the programs, both in terms of the method of delivering and developing affection and the experience of the mentors. However, there is still a weakness in terms of the lack of dialogue between the counsellors and the participants, the lack of discussion of experiences and facts about family life, and case studies.